Anti-inflammatory effects of Samsoeum, a Korean medicine for health insurance, on chronic bronchitis caused by lipopolysaccharide in rats. Issue 8 (15th July 2020) - Kim, Mi Hye; Lee, Sun Haeng; Jin, Seong Chul; Choi, In Yeong; Song, Eun Hye; Ham, Seong Ho; Yang, Woong Mo
Abstract : Samsoeum (SSE), a Korean medicine, has been used to treat upper respiratory infection including residual coughs after catching a cold, and colds in patients with gastrointestinal disorder. Abstract : Background : Samsoeum (SSE), a Korean medicine, has been used to treat upper respiratory infection including residual coughs after catching a cold, and colds in patients with gastrointestinal disorder. In this study, we investigated the inhibitory effect of SSE against lipopolysaccharide (LPS)-induced bronchitis and characterized its optimal dosing range based on the improvement of SSE concentrations. Materials and methods : Male Sprague Dawley rats were intra-nasally administered LPS on day 0, 3 and 6. 2 g kg −1 dose of SSE for rat was determined by the human equivalent dose formula and orally administered once a day from day 3 to day 6. To clarify the optimal administration dose of SSE, various doses including 0.5 (1/4 fold), 1 (1/2 fold), 6 (3 fold), 12 (6 fold), 24 (12 fold) and 36 g kg −1 (18 fold) were also orally administered. In addition, the molecular mechanism of SSE in mucin hyperproduction was investigated in LPS-sensitized A549 cells. Results : Oral administration of SSE ameliorated alveolar wall thickening and inflammatory cell infiltration of lung tissues in LPS-induced bronchitis at doses of 1/4 fold, 1/2 fold and 1 fold. The total cell and neutrophil numbers in bronchoalveolar lavage fluid (BALF) were reduced in the SSE-treated groups compared with the LPS group. In addition, 0.5, 1 and 2 g kg −1 of SSE suppressed LPS-induced mucin glycoprotein 5AC (MUC5AC) production in BALF. Furthermore, SSE treatment significantly inhibited the pro-inflammatory cytokines, resulting in the decrease of MUC5AC production by the JAK1/STAT6 signaling pathway. Conclusions : 1, 2 and 6 g kg −1 of SSE ameliorated chronic bronchitis by inhibiting LPS-induced neutrophil infiltration and MUC5AC release in BALF. These findings suggested that SSE with 0.5–3-fold of general daily intake dose would be a therapeutic agent for chronic bronchitis.